E-WOM messaging on social media: Social ties, temporal distance, and message concreteness. Issue 3 (5th June 2017) - Choi, Yung Kyun; Seo, Yuri; Yoon, Sukki
Abstract : Purpose: The purpose of this paper is to explore the intentions to share electronic word-of-mouth (E-WOM) messages on social media websites depending on tie strength, perceptions of temporal distance and the concreteness of promotional messages. Design/methodology/approach: A 2×2×2 mixed design is used. Temporal distance (near vs distant) and message concreteness (text vs picture) are between-subjects factors; sharing intentions (close friends vs general public) is a within-subjects factor. Findings: Findings indicate that consumers are more likely to share promotional messages with their strong rather than weak ties. If they perceive that purchases will occur soon, concrete promotional messages will more strongly motivate them to share the message with their friends. However, if they perceive that purchases will occur in the distant future, abstract messages are more motivating. The difference occurs because construal-level theory is more effective among strong E-WOM ties. Originality/value: By studying senders' perspectives, the authors make a new theoretical and practical contribution to the emerging literature on E-WOM communication. Specifically, the authors show how senders are persuaded to share information with their strong- or weak-tie audiences according to the concreteness of a message and temporal distance. The authors add construal-level theory and advertising message processing to the domain of E-WOM and social ties research.